Pediatric Short Bowel Syndrome: Predicting Four-Year Outcome after Massive Neonatal Resection - Capriati, Teresa; Giorgio, Daniela; Fusaro, Fabio; Candusso, Manila; Schingo, Paolo; Caldaro, Tamara; Laureti, Francesca; Elia, Domenica; Diamanti, Antonella (European Journal of Pediatric Surgery, 2018)
Objectives The aim of this study was to ascertain predictors of survival, liver disease (LD), and enteral autonomy 48 months after resection in neonatal short bowel syndrome (SBS) patients with residual small bowel length (SBL) ≤40 cm.Patients and Methods Medical records of all SBS patients followed up between 1996 and 2016 were retrospectively reviewed. Survival rate, prevalence of LD, and of enteral autonomy were evaluated.Results Forty-seven patients were included, and 43 were still alive at the end of the study period, with cumulative 48-month survival of 91.5%. Twenty-one (45%) patients developed LD, all within the first 6 months. On the final follow-up visit, three (6%) patients were still jaundiced and progressed toward end-stage LD. LD prevalence was higher in patients with recurrent bloodstream infections (odds ratio [OR] 5.4, 95% confidence interval [CI] 1.5–19.3). Of the 43 surviving patients, 22 (51%) had enteral autonomy 48 months after resection. The probability of weaning off parenteral nutrition (PN) was strongly correlated with the remaining SBL.Conclusion Survival of patients who have undergone neonatal massive small bowel resection has improved in recent years. Multidisciplinary strategies can improve the course of LD, but not the probability of weaning off PN, which seems to be strongly dependent on the anatomical profile of residual bowel. Therefore, the primary surgical approach should be as conservative as possible to gain even small amounts of intestinal length, which may be crucial in promoting intestinal adaptation.
Keywords: intestinal failure; short bowel syndrome; pediatric; enteral adaptation